Pemanfaatan Lumpur Hasil Samping IPAL Pabrik Pasta Gigi Sebagai Bahan Baku Batako Dalam Upaya Reduksi Limbah - Dwi Ratri Mitha Isnadina; Raih Panji Sampoerna; Nita Citrasari (Fakultas Teknologi Mineral, Universitas Pembangunan Nasional (UPN), 2018)
This research were aimed to know the best variation as brick raw materials according to SNI 03-0349-1989 about Concrete Brick for Wall Pairs and to know Pb concentration in leachate from raw material mixture and from stabilization-solidification product. Sludge from Wastewater Treatment Plant’s Toothpaste Factory was used as a substitution of Portland cement which was varied to 10%, 30% and 50% of Portland cement. Batako were tested by external views and physical requirements according to SNI 03-0349-1989. Raw material and product of brick were analyzed by TCLP for Pb metal using Atomic Absorption Spectrophotometric method. The selected sample variation as a large hollow brick material based on SNI 03-0349-1989 is 30% of sludge substituting Portland cement with grade II quality. The concentration of Pb in leachate of brick raw material for each variation was 0.84 mg / L; 0.95 mg / L; and 1.02 mg / L. While the concentration of Pb in the leachate of brick for each variation was 0.40 mg / L; 0.45 mg / L; and 0.49 mg / L.